Who Profits from Trading Options? - Hu, Jianfeng; Kirilova, Antonia; Park, Seongkyu (Gilbert); Ryu, Doojin (Management Science, 2024)
We use account-level transaction data to examine trading styles and profitability in a leading derivatives market. Approximately 66% of active retail investors predominantly hold simple, one-sided positions in only one class of options, whereas institutional investors are more likely to use complex strategies. Hypothesizing that the complexity of trading styles reflects investors’ skills, we examine the effect of options trading styles on investment performance. We find that retail investors using simple strategies lose to the rest of the market. For both retail and institutional investors, selling volatility is the most successful strategy. We conclude that these style effects are persistent and cannot be fully explained by systematic risk exposure. This paper was accepted by Lukas Schmid, finance. Funding: J. Hu acknowledges financial support from Lee Kong Chian Fellowship. A. Kirilova acknowledges financial support from the Spanish Ministry of Science and Innovation [Grant PID2021-128994NA-I00]. Supplemental Material: The online appendix and data are available at https://doi.org/10.1287/mnsc.2023.4916 .